2008
DOI: 10.2991/jnmp.2008.15.s3.31
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Expansion and Integrability Properties of the Lattice Potential KdV Equation

Abstract: We apply the discrete multiscale expansion to the Lax pair and to the first few symmetries of the lattice potential Korteweg-de Vries equation. From these calculations we show that, like the lowest order secularity conditions give a nonlinear Schrödinger equation, the Lax pair gives at the same order the Zakharov and Shabat spectral problem and the symmetries the hierarchy of point and generalized symmetries of the nonlinear Schrödinger equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Then, by a paradox, they showed that a C-integrable equation must reduce to a linear equation or another C-integrable equation as the Eckhaus equation [4,22]. In the case of discrete equations it has been shown [26,1,16,18,17,19,10,11,12] that a similar situation is also true. One presents the equivalent of the Calogero-Eckhaus theorem stating that a necessary condition for a nonlinear dispersive partial difference equation to be S-integrable is that the lowest order multiple scale expansion on C (∞) functions give rise to integrable NLSE.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by a paradox, they showed that a C-integrable equation must reduce to a linear equation or another C-integrable equation as the Eckhaus equation [4,22]. In the case of discrete equations it has been shown [26,1,16,18,17,19,10,11,12] that a similar situation is also true. One presents the equivalent of the Calogero-Eckhaus theorem stating that a necessary condition for a nonlinear dispersive partial difference equation to be S-integrable is that the lowest order multiple scale expansion on C (∞) functions give rise to integrable NLSE.…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in [10,11,17], the introduction of multiple scales on a lattice reduces the given discrete equation either to a local nonlinear PDE, by imposing a slow-varying condition, or to a PDE of infinite order when dealing with analytic functions. Here we choose the second alternative because, as shown in [10,11], only in this case are the integrability conditions of the discrete equation preserved.…”
Section: Introductionmentioning
confidence: 99%
“…An integrable partial differential equation, as the NLS equation ( 1), has an asymptotic integrability of infinite order. Some attempts to extend this approach to discrete equations have been proposed [6,[16][17][18][23][24][25]. In [23][24][25], a multiscale technique for dispersive Z 2 lattice equations has been developed which is based on the dilation transformations of discrete shift operators.…”
Section: Introductionmentioning
confidence: 99%